Fractographic study into the effect of drilling damage on bearing mechanisms and performance in carbon-fibre epoxy composites - Greenhalgh,ES; Canturri,C; Katafiasz,TJ (Engineering Failure Analysis, 2021)
With the widespread adoption of polymer composites in primary structures, understanding and prediction of the performance of composite to metal hybrid joints is now critical to engineering design of transport structures. This work investigated the damage processes associated with bearing failure of such composite joints, for both pristine holes and holes damaged during drilling. An aerospace grade composite was drilled under three different conditions, tested to failure under quasi-static double bearing loading, and then characterised using fractographic techniques. In the pristine condition, the initial damage process was 0° longitudinal splitting tangential to the lateral extents of the hole which then dictated the extent of the subsequent bearing damage development. Beneath the bearing face of the hole inclined lines of in-plane microbuckled fibres had developed whilst beyond the constraint of the washer there was considerable delamination and massive out-of-plane fibre microbuckling. As the degree of drilling damage increased, 0° longitudinal split development was inhibited, and the local pre-existing damage at the periphery of the hole had extended into the bearing damage zone, directly initiating out-of-plane fibre microbuckling. Consequently the bearing damage zone exhibited irregular distributions of fibre microbuckles, both across the thickness and depth beneath the bearing face of the hole. The observations in this work provide a means to validate predictive models and offer potential routes to improve bearing performance and the tolerance of laminates with drilling damage when under bearing loads.